A randomized controlled pilot study of a proprietary combination versus sunscreen in melasma maintenance. - Chatterjee, Manas; Neema, Shekhar; Rajput, Gopalsing Rameshsing (Indian Journal of Dermatology, Venereology & Leprology)
Background: Melasma is the commonest cause of facial hypermelanosis in skin type IV-VI. First-line treatment includes a triple combination containing topical corticosteroid and hydroquinone which have side effects on prolonged use. Chemical peels are a second-line management option with the laser being used in refractory cases, but the worsening of hyperpigmentation in darker skin types can occur following laser therapy. Sunscreen is a must to prevent relapses.Aims and Objectives: (i) To compare the effects of treatment with a proprietary combination (phenyl ethyl resorcinol, nonapeptide-1, aminoethyl phosphinic acid, antioxidants and sunscreen) versus sunscreen alone in limiting or reducing, melasma and preventing recurrence as a maintenance regimen after the initial use of triple combination,(ii) to evaluate the safety of the formulation studied, and (iii) to study the improvement of the quality of life of the patients after using the study formulation versus placebo.Methods: It was a prospective double-blinded parallel-group randomized controlled pilot study. A total of 46 subjects were recruited by consecutive sampling methods and randomized to 23 each in case and control groups. The study period was eight months with three phases. Phase 1 constituted the application of triple combination for eight weeks by both groups followed by phase 2 with the case group applying proprietary medicine and the control group applying sunscreen. Phase 3 was a follow-up period to see the sustenance of results in both groups as well as any evidence of relapses. Sunscreen was applied in all three phases.Results: Case group in the study showed improvement in the melasma severity score and mean melanin index as measured by mexameter but it did not attain statistical significance as compared to the control group. The melasma area and severity index score showed a consistent reduction in the case group, whereas it increased in the control group from baseline.Limitations: Small sample size and a short follow-up period of our study were major limitations.Conclusion: The proprietary combination, which has sunscreen as one of its constituents, is more effective in maintaining remission after triple combination without any added inconvenience of application of two separate preparations as compared to sunscreen alone.